Dataset of China Kuroshio Extension Observatory (CKEO): Moored Buoy Observations in the Kuroshio–Oyashio Transition Zone - Zhaohui Chen; Yueqi Zhang; Ruichen Zhu; Zhongxiang Fan; Jia-Zhen Wang; Xin Ma; Guoqing Ren; Haiyuan Yang; Lixiao Xu; Xiaopei Lin; Lixin Wu (Advances in Atmospheric Sciences, 2026)
The Kuroshio–Oyashio Transition Zone (KOTZ) serves as a vital dynamic interface between the warm Kuroshio Extension and the cold Oyashio Current. However, severe sea conditions with strong ocean currents, winds and waves pose challenges for sustained in situ observations of both oceanic and atmospheric variables. This paper introduces the China Kuroshio Extension Observatory (CKEO), a moored observatory program designed for long-term observations in the KOTZ. We provide a dataset of meteorological and oceanographic properties, including sea surface wind, air temperature, atmospheric pressure, relative humidity, sea surface temperature, sea surface salinity, ocean currents in the upper 100 m, and temperature profile in the upper 500 m. The CKEO, which began operations in 2019, provides a continuous air–sea observational dataset of the KOTZ to the scientific community and advances the understanding of multiscale physical processes in this region.

Postharvest application of plasma-activated water to extend shelf life of strawberries - Yingman Gao; Yupan Zhu; Panfeng Guan; Leiyi Zhang; Xinyue Li; Guihuan Wei; Chenbin Hu; Ruichen Sha; Nanshan Du; Ruonan Ma; Zhen Jiao; Bing Li (Food Chemistry, 2026)

Tuning surface residual lithium into a Li-ion-conductive protective interphase toward stable Ni-rich cathodes - Shumin Liu; Huangzhang Zhou; Wenhao Jia; Yingjie Sun; Peng Gao; Ruichen Zhu; Yongming Zhu; Xudong Li; Liguang Wang (Chemical Engineering Journal, 2026)

Femtosecond laser-fabricated defect-rich PtRe alloy clusters for enhanced alkaline hydrogen evolution - Xianze Zhang; Junwen Xiong; Zhiyi Sun; Ruichen Lu; Zikang Su; Chen Zhang; Qimiao Zhu; Shilong Yuan; Lan Jiang; Shengjie Xia; Liquan Sun; Xingdong Wang; et al. (Chemical Engineering Journal, 2026)

Postharvest application of plasma-activated water delays anthracnose symptom development in apples - Yingman Gao; Ruichen Sha; Guihuan Wei; Lingling Yang; Yupan Zhu; Yudong Liu; Ruonan Ma; Zhen Jiao; Bing Li (Postharvest Biology and Technology, 2025)

Upcycling PET waste into carbon quantum dots as flame retardant of PET for closed-loop recycling - Jianfei Wei; Guocong Ma; Yaoyao Tang; Jing Zhang; Gaoling Jin; Chaohui Ma; Linhan Bing; Zhiguo Zhu; Zhenfeng Dong; Puzhen He; Ruichen Zhou; Rui Wang; et al. (Chemical Engineering Journal, 2025)

Palbociclib inhibits the progression of head and neck cancer and improves the Cetuximab response under specific condition in vitro and in vivo - Ruichen Li; Qi Wang; Yang Zhao; Yi Zhu; Xiaoshen Wang (Molecular Biology Reports, 2024)

Temporal and spatial variations in squid jigging catch efficiency in the Oyashio Extension region - Zixuan Niu; Zhaohui Chen; Wei Yu; Haihong Guo; Ruichen Zhu; Xiaoyi Zhang (Fisheries Oceanography, 2024)
The abundance of fishery resources significantly impacts the ratio of fishing effort to harvest. However, traditional statistics of fishery catches or commonly used catch per unit effort (CPUE) metrics cannot accurately capture the complexity of resource abundance in the ocean. To address this issue, we propose here a novel approach that integrates the actual fishery catch from vessel logs with fishing duration obtained through automatic identification system (AIS) positioning. This combined analysis eliminates confounding factors and introduces a novel metric called “catch efficiency (CE)” to evaluate fishing operations more accurately, thereby reflecting resource abundance in a more reasonable way. In this study, we focus on the CE of squid in the Oyashio Extension region in the Northwestern Pacific. Our analysis reveals significant temporal and spatial variations of CE, manifesting in both intensity and distribution patterns. Moreover, our findings establish a close relationship between CE and background water mass distribution, chlorophyll‐a concentration, and micronekton biomass. This implies that the resource abundance of squid can be inferred by considering the varying environmental factors within the fishing area.

Defect-rich perforated PdFe bimetallene for the efficient electrochemical oxidation of glycerol - Xiaojun Chu; Ruichen Geng; Zekai Shen; Yaxuan Li; Xiaorui Fan; Zhaoyou Zhu; Yinglong Wang; Shuli Yin (Chemical Engineering Journal, 2024)

Numerical investigation of pyrolysis coking characteristics of supercritical hydrocarbon fuels in sinusoidal cooling channels - Mingyin Zhu; Huaizhi Han; Ruichen Gao; Bensheng Xie (Fuel, 2023)